Response surface optimization of bioremediation of Acid black 52 (Cr complex dye) using Aspergillus tamarii. Issue 3 (1st February 2017) - Ghosh, Arpita; Dastidar, Manisha Ghosh; Sreekrishnan, T. R.
ABSTRACT: Bioremediation of the Cr complex dye (Acid black 52) was performed in batch and continuous modes using growing Aspergillus tamarii . The removal of Cu which may be present as an impurity was 100% at 100 mg/L initial dye concentration. The removal of color and Cr decreased from 87% to 4% and from 92% to 8%, respectively, by increasing dye concentration from 100 to 5000 mg/L in batch mode. The removal of color and Cr increased from 27% to 67.8% and from 32% to 72%, respectively, with increasing hydraulic retention time from 28 to 220 h at 100 mg/L dye concentration in continuous mode. For optimization of color removal using response surface methodology (RSM) the ranges of parameters were kept at dye concentration: 200–500 mg/L; pH: 4–6 and time: 35–50 hours. Maximum color removal suggested by the model was 85.6809% at initial dye concentration 200 mg/L, pH 5.25 and time 50 h. The validation experiments in batch and continuous modes were conducted at the optimum conditions as suggested by the RSM model. The theoretical and experimental responses of color removal were in close agreement in batch mode. The scanning electron microscopy, energy dispersive X-ray analysis, transmission electron microscopy and gas chromatography–mass spectroscopy analyses indicated biosorption and biodegradation of dye.